SATRATEGI MENGAJAR MENULIS CERPEN BERBASIS TEKNOLOGI BERMUATAN KEBUDAYAAN - Saenal Masri; Fathanah Syamsuddin; Akram Budiman Yusuf (STKIP Subang, 2024)
Learning to write short stories currently faces big challenges, especially because the material is less interesting and the results of student work are less than satisfactory. Writing short stories requires complex skills, including understanding the material, creativity, imagination, and mastery of diction. One of the innovative solutions proposed is the use of short stories in digital form, which can increase student interest and motivation. Digital technology allows students to share their work widely, get feedback, and improve the quality of their writing. Apart from that, the integration of local cultural values, such as traditions and folklore of the Bugis tribe from South Sulawesi, in teaching materials can enrich learning and instill a love of local culture. This research uses a library research method to examine related literature and proposes a concept for teaching materials that combine digital short stories with the cultural values of the Bugis tribe. In this way, it is hoped that learning to write short stories can be created that is more interesting, effective and meaningful for students.